Pengembangan Sistem Pengontrolan Irigasi Cerdas dengan Teknologi Internet of Things (IoT) - Ali Abrar; Tukino Tukino (LPPM Universitas Putera Batam, 2023)
Agriculture plays a pivotal role in addressing global food demands, with efficient resource utilization, particularly water, being crucial for sustainability. In this context, the Internet of Things (IoT) has emerged as a potent tool for optimizing irrigation water usage. This study centers on developing an IoT-based smart irrigation control system to enhance agricultural water efficiency. The system integrates soil moisture sensors, water pumps, and an IoT platform for autonomous plant irrigation management. Real-time sensor data is collected and processed to make intelligent irrigation decisions, reducing water consumption by up to 30% compared to traditional methods, as demonstrated in field trials. Beyond water efficiency, the system empowers farmers to remotely access and manage irrigation through a web or mobile app, offering resource management flexibility and improved adaptability to changing weather conditions. This research underscores IoT's substantial potential in advancing agricultural irrigation efficiency, curbing water use, and promoting economically and environmentally sustainable farming. These findings serve as a blueprint for future agricultural solutions in the IoT-driven sector.